Mathematical Literacy Ability of Junior High School Students in Metro City - Salma Nurjannah; Saiful Mahfud; Endah Wulantina; Putri Mega Aulia; Wishnu Aditya Mahendra; Khusnul Mafatir; Hana Umniyati (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2026)
International studies, such as PISA 2022, show that Indonesian students' mathematical literacy is still relatively low. This study aims to determine the mathematical literacy ability of junior high school students in Metro City using quantitative methods. The research sample consisted of 248 students from 9 public junior high schools, selected via cluster random sampling: one class per school. Data were collected through a mathematical literacy test consisting of five essay questions and analyzed according to the ability criteria of Ebel and Frisbie. The results showed that students' average mathematical literacy score was 7.78 out of a maximum ideal score of 20. Most students were in the low and very low ability categories, indicating that the level of mathematical literacy in Metro City remains low. When viewed by sub-domain, students' abilities in algebra and statistics were in the moderate category, their abilities in numbers were in the low category, and their abilities in geometry were in the very low category. These findings indicate the need for further efforts to improve students' mathematical literacy, especially in numbers and geometry.